2011
DOI: 10.1002/ardp.201100309
|View full text |Cite
|
Sign up to set email alerts
|

4H‐1,4‐Benzothiazine, Dihydro‐1,4‐benzothiazinones and 2‐Amino‐5‐fluorobenzenethiol Derivatives: Design, Synthesis and in vitro Antimicrobial Screening

Abstract: As part of our studies focused on the design and synthesis of new antimicrobial agents a series of 7-fluoro-3,4-dihydro-2H-1,4-benzothiazine derivatives (4a-4f, 4h) and 7-fluoro-2H-1,4-benzothiazin-3(4H)-one analogues (4j-4o) were synthesized and evaluated for their in vitro inhibitory activity against a representative panel of Gram-positive and Gram-negative bacteria strains and also toward selected fungi species. These compounds were prepared in one step from chloro-substituted-2-amino-5-fluorobenzenethiol 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Moreover, the importance of CYP51 as a plausible target in the treatment of C. albicans infections has been already and successfully reported [23e25]. On the basis of this evidence, compounds 1bei were therefore docked into the catalytic site of the homology based model of C. albicans CYP51 (CA-CYP51) [26,27] which has already been successfully used in a previous study on antifungal agents [7]. Docking binding poses highlighted some interesting features that might be in charge of the antifungal activity of the 4-ClePheO compounds under study.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the importance of CYP51 as a plausible target in the treatment of C. albicans infections has been already and successfully reported [23e25]. On the basis of this evidence, compounds 1bei were therefore docked into the catalytic site of the homology based model of C. albicans CYP51 (CA-CYP51) [26,27] which has already been successfully used in a previous study on antifungal agents [7]. Docking binding poses highlighted some interesting features that might be in charge of the antifungal activity of the 4-ClePheO compounds under study.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%
“…Results showed that the SH moiety at the 2 position of the heterocyclic nucleus led to a remarkable antibacterial activity. In a search for new leads toward potent antimicrobial agents, given the isosteric relationship existing between SH and NH 2 groups, following a previous work [7], we synthesized a series of 2-amino-1,3-benzothiazoles ( Fig. 1) and tested their in vitro antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…As long as this evidence is concerned, compound 2f was therefore docked into the catalytic site of the homology‐based model of C . albicans CYP51, which was successfully used in a similar study on structurally related antifungal agents . Dockings binding poses some highlighted, interesting features that might be in charge of the antifungal activity of 2f and also of the synthesized congeners.…”
Section: Resultsmentioning
confidence: 74%
“…Recently, related research has been focused on existing molecules and their modifications in order to reduce their side effects and to explore their other pharmacological and biological effects (Sebbar et al, 2016a;Armenise et al, 2012). As a continuation of our research work on the development of N-substituted 1,4-benzothiazine derivatives and the evaluation of their potential pharmacological activities, we have studied the condensation reaction of propargyl bromide with (Z)-2-(2-chlorobenzylidene)-2H-1,4-benzothiazin-3(4H)-one under phase-transfer catalysis conditions using tetra-n-butylammonium bromide (TBAB) as a catalyst and potassium carbonate as the base, giving the title compound in good yield (Sebbar et al, 2016b, Ellouz et al, 2017a.…”
Section: Structure Descriptionmentioning
confidence: 99%